1999
DOI: 10.1088/0953-4075/32/22/307
|View full text |Cite
|
Sign up to set email alerts
|

Strong projectile dependence of C60fragmentation by MeV-energy heavy ions

Abstract: Experimental results are presented for ionization and fragmentation of C60 bombarded by various projectile ions of H+, Li1,2+, B1,2+, O2+, Si1,2+, Ag2+ and Au3+ with velocities 0.9v0-3v0 (v0: Bohr velocity). Mass distributions of light fragment ions Cn+ (n = 1-12) are found to change drastically depending on the projectile species or atomic number Zp. The result indicates that multifragmentation of C60 takes place at small impact parameters where the projectile nuclear charge is less screened. It is found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
5
19
0
Order By: Relevance
“…For the estimation of the internal electronic excitation energy, we used the knowledge that the total energy transferred to the electrons in a target molecule (E d ) is divided among the excited and purely ionized electrons with a certain partition rate, α, on average over impact parameter [3,[20][21][22][23]. Then, the internal electronic excitation energy E int is given by E int = (1 − α)E d and the energy transferred to the purely ionized electrons E ion is expressed by E ion = αE d .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the estimation of the internal electronic excitation energy, we used the knowledge that the total energy transferred to the electrons in a target molecule (E d ) is divided among the excited and purely ionized electrons with a certain partition rate, α, on average over impact parameter [3,[20][21][22][23]. Then, the internal electronic excitation energy E int is given by E int = (1 − α)E d and the energy transferred to the purely ionized electrons E ion is expressed by E ion = αE d .…”
Section: Discussionmentioning
confidence: 99%
“…In Table I the estimated values of E int are presented for n i = 2-7. We would like to point out that the fragment patterns for various projectile ions in the MeV region were found to be governed by E int estimated with α and β for each projectile and its velocity [3].…”
Section: Discussionmentioning
confidence: 99%
“…), energy losses of about 350 eV were observed [2]. Also, in MeV collisions, Tsuchida et al found indications for fragmentation due to electronic stopping [3].…”
Section: Kvi Atomic Physics Rijksuniversiteit Groningen Zernikelaanmentioning
confidence: 99%
“…As the molecular fragmentation occurs predominantly from a dissociative excited state, it is important to measure KER in individual fragmentation channels because it carries direct information about the initial dissociative excited states [8,14]. The amount of electronic energy deposition into a target molecule is the essential quantity that characterizes the fragmentation of molecules ranging from diatomic [3] to polyatomic [15] and cluster particles [16].…”
mentioning
confidence: 99%